Natural justice in the decision-making process of the security council: myth and reality - Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali; Masum, Ahmad; Mohamed Nafees, Seeni; Eishan Jan, Mohammad Naqib (CLJ Malaysia Sdn Bhd, 2024)
The Security Council is primarily responsible to maintain international peace and security in accordance with the purposes and principles of the UN on behalf of its members. Thus, it is not at liberty to act as it wishes in discharging its duties. Generally, it maintains global peace in two ways, i.e., by recommending peaceful resolutions to international disputes and, when necessary, resorting to enforcing action in the form of economic and political sanctions or even military intervention. The Council is mainly composed of the five permanent members and 10 non-permanent members to ensure swift decision-making in matters of international peace and security. Despite the fact that only 15 members participate in the Security Council decisions, these decisions are binding on all the UN members. This makes it very powerful organ of the UN with quasi-executive, quasi-legislative and quasi-judicial power at the international level. Ironically, the decision-making processes at the Security Council often deviate from the principle of natural justice. Justice should be the ultimate objective in any kind of proceeding and administration decisions in line with the principles of natural justice. procedures. Hence, it is crucial for the Security Council to ensure its minimum protection of the rights of individual against arbitrary and "nemo judex in causa sua. These principles are used to provide justice based on the two Latin maxims, namely, "audi alteram partem" decision-making. Common law develops two principles of natural justice.